2013
DOI: 10.1136/archdischild-2013-304540
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the effects of colistin therapy in children with multidrug-resistant Gram-negative bacterial pathogens: impact of HIV status on outcome

Abstract: HIV-infected children had poorer clinical and bacteriological responses to colistin treatment than HIV uninfected/unexposed. These results require confirmation with prospective studies to determine whether findings are due to poor microbial response, immunodeficiency or repeated reinfections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These organisms are common nosocomial microbes. 5 Similarly, a study on colistin usage in neonates in Turkey, by Cağan et al, 9 found that the most frequently isolated pathogens were K. pneumoniae and A. baumannii followed by P. aeruginosa and E. cloacae. The same study reported that patients treated with colistin were treated with at least one other antibiotic, a finding that is mirrored in this study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These organisms are common nosocomial microbes. 5 Similarly, a study on colistin usage in neonates in Turkey, by Cağan et al, 9 found that the most frequently isolated pathogens were K. pneumoniae and A. baumannii followed by P. aeruginosa and E. cloacae. The same study reported that patients treated with colistin were treated with at least one other antibiotic, a finding that is mirrored in this study.…”
Section: Discussionmentioning
confidence: 96%
“…3,4 Microbial resistance to antibiotic classes such as cephalosporins, aminoglycosides, quinolones and carbapenems has contributed to an increase in the use of colistin globally. 5 In South Africa (SA), colistin is used as salvage therapy for life-threatening infections, 1,2 especially where resistance to the carbapenem class of antibiotics has been observed. 6 The carbapenems have been considered to be part of the last line of defence against MDR gram-negative bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although limited studies have evaluated safety and efficacy of colistin in pediatrics and neonates, the results were promising [74][75][76]. Response rate of 53-87.5% were noted in pediatric and neonatal studies.…”
Section: Neonates and Pediatricsmentioning
confidence: 81%